Control of deformability during drawing of low‑carbon wire rod - V. P. Fetisov (Литьë и металлургия)
The maximum drawing of the wire rod with a single drawing characterizes its deformation ability to extremely large total compressions. A complex index of deformability of a low-carbon wire rod determined under tension is proposed, taking into account the ability of the metal to harden and its tendency to localize plastic deformation.